Hochuekkito accelerates recovery from cisplatin induced-muscle atrophy accompanied by slow-twitch fiber-specific microRNA upregulation in mice - Sekine, Hitomi; Matsumoto, Chinami; Fujitsuka, Naoki; Mogami, Sachiko; Ohnishi, Shunsuke; Takeda, Hiroshi (Frontiers in Pharmacology, 2025)
IntroductionCis-diamine-dichloro-platinum (II) (cisplatin) is a widely prescribed anticancer drug known to induce severe side effects, including skeletal muscle atrophy. As muscle atrophy negatively impacts the prognosis and survival of cancer patients, elucidation of its pathogenesis and development of preventive and treatment methods is important. Hochuekkito (HET), a Japanese Kampo medicine, has been reported to improve decreased physical activity and muscle weight in various animal models, but not in cisplatin-induced muscle atrophy. Therefore, this study aimed to clarify the characteristics of cisplatin-induced muscle atrophy and the therapeutic effects of HET, especially with emphasis in the recovery phase.MethodEight-week-old male C57BL/6J mice were administered with cisplatin (3 mg/kg/day, intraperitoneally) from Day0 to Day3 and provided HET-containing food from 2 weeks before cisplatin administration until Day14. Muscle weight and performance were evaluated and the underlying mechanisms were investigated by using gene expression, immunohistochemistry, and microRNA (miRNA)-sequence analyses.ResultsCisplatin administration continued to reduce gastrocnemius muscle weight until Day14, even after recovery from transient decrease in food intake and body weight and was accompanied by decreased locomotor activity and grip strength, presumably due to the continuous suppression of the mRNA expression of Myogenic differentiation 1. Although HET did not suppress the activation of muscle protein degradation or increase myogenic regulatory factor expression, it restored decreased locomotor activity and gastrocnemius muscle weight by inducing an increase in the weight of the red muscle region, which contains slow-twitch fibers. Immunohistochemical analysis showed that red muscle slow-twitch fiber cross-sectional area was increased by HET treatment. The levels of miRNAs involved in muscle atrophy and aging, such as miR-29a/b and miR-34a, were increased by cisplatin; conversely, HET increased the expression of miR-1a-1 and miR-1a-2, which reportedly enhance muscle differentiation, and miR-206, which enhances slow muscle fiber differentiation and thickening.ConclusionHET increased locomotor activity and muscle weight in cisplatin-induced muscle atrophy model mice, probably by enhancing myogenesis in slow-twitch fibers, which was related to miRNA expression changes. Thus, HET may be useful in treating cisplatin-induced muscle atrophy.